2019
DOI: 10.1002/arch.21588
|View full text |Cite
|
Sign up to set email alerts
|

Boric acid‐induced immunotoxicity and genotoxicity in model insectGalleria mellonellaL. (Lepidoptera: Pyralidae)

Abstract: Boric acid (BA) is widely used in various industrial process and can be accessed to nontarget organisms. This study aimed to investigate the insecticidal effects of BA and its toxic activities with respect to immunologic and genotoxic effects using Galleria mellonella larvae as a model. BA concentrations (78.125–10,000 ppm) were administrated to the larvae using the feeding method. Concentration‐dependent mortality was observed in all larval groups. Probit analysis revealed LC30, LC50, and LC70 values to be 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…We did not see evidence of growth and replication of hemocytes in our study. It is likely that hemocytes require the presence of additional factors in order to replicate 23 . Yamashita and Iwabuchi 16 reported that prohemocytes from Bombyx mori were more likely to divide if larval hemolymph was included in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…We did not see evidence of growth and replication of hemocytes in our study. It is likely that hemocytes require the presence of additional factors in order to replicate 23 . Yamashita and Iwabuchi 16 reported that prohemocytes from Bombyx mori were more likely to divide if larval hemolymph was included in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Another mode of action of boric acid is the abrasiveness of the particles to the insect cuticle, 30,35,36 which may favor pest mortality when the element is applied onto the plants during fertilization. The use of this micronutrient via leaf is able to control diseases in brassicas, 15 therefore, such management can also cause the mortality of P. xylostella by topic application, which was not studied in this research.…”
Section: Resultsmentioning
confidence: 99%
“…11 Boric acid has been pointed out as effective for the control of several urban pests, 29 but one recent work has reported its effectiveness on Galleria mellonella L. (Lepidoptera: Pyralidae) larvae, an economically important agricultural insect-pest, killing this pest by ingestion. 30 The high mortality from consumption of boric acid may be related to the damage that this element can cause in the insect gut wall. 31 Since the application of boric acid via leaf in brassicas is able to increase the translocation of the micronutrient, being the most efficient way to make this element available within the plant, 32 the ingestion by P. xylostella larvae may have led them to death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total hemocyte count has been evaluated as an important marker in many studies on the immunity of the model organism G. mellonella (Er et al, 2010;Altuntaş et al, 2012;Er and Keskin, 2015;Kurt and Kayış, 2015;Gwokyalya and Altuntaş, 2019;Kaya et al, 2021a,b). In the aforementioned literatures, the increase in the number of hemocytes is generally interpreted as supporting immunity.…”
Section: Resultsmentioning
confidence: 99%